COMPUTER TOMOGRAPHIC ANGIOGRAPHY BEFORE AND AFTER EXTRA-INTRACRANIAL MICROANASTOMOSIS (World Bulletin of Public Health, 2025)
This article describes computed tomographic angiography of the brachiocephalic arteries of the brain before and after extra-intra-intracranial microanastomosis.